PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI STUDI KASUS PADA MILK AND FOOD POM SABA EMBE - Taopik Hidayat; Neng Sri Wulandari (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine the effect of price and product quality on buying interest in Milk and Food Pom Saba Embe Garut. This researcher uses a quantitative method, multiple correlation with a survey technique on a sample of 68 people. The population of this study is Milk And Food Pom Saba Embe Garut consumers. The test results obtained a value of 0.812 indicating that there is a very strong influence between price (X1) and product quality (X2) which have a joint effect on buying interest (Y). The coefficient is between the interval of the coefficient 0.80 – 1.000. Furthermore, there is a Fcount value of 62.968 > Ftable of 2.75 and for a sig value of 0.000 <0.05 so it can be concluded that the hypothesis is accepted which means there is a positive influence between (X1) price and (X2) product quality simultaneously on buying interest (Y). This conclusion is also strengthened by testing the coefficient of determination. The results of the test for the coefficient of determination show that the contribution of price (variable X1) and product quality (X2) to purchase intention (variable Y) at Milk And Food Pom Saba Embe Garut is 66% and the remaining 34% is influenced by other variables not examined.